A theoretical and experimental framework for the formation of mixed anodic films on combinatorial aluminium-cerium alloys. (20th January 2021) - Shahzad, Khurram; Lone, Shaukat Ali; Mardare, Cezarina Cela; Mardare, Andrei Ionut; Hassel, Achim Walter
Highlights: Aluminium-Cerium combinatorial library was anodized in phosphate buffer by SDCM. Ce influenced the morphology of parent alloys and anodic films dielectric properties. Cerium induces amorphization in the parent alloys. Up to 10.5% Ce does not reduce the mixed oxide stability but increases the hardness. Abstract: Anodizing promises fast, cost-effective, and precise fabrication of mixed metal oxides from alloys of complex chemistries and compositions. Applicable to a whole class of valve metals and their alloys, this versatile fabrication method has found new dimensions of its applicability to a unique combination of valve and non-valve metals in the quest of finding new applications. Hereby the fabrication of anodic passive films on Al-Ce thin-film combinatorial alloy library covering 1.5 to 10.5 at.% Ce in a phosphate buffer electrolyte having pH = 8.3 is demonstrated. Few nanometre thin dielectric films were attained through the automated localized anodizing using scanning droplet cell microscopy (SDCM). Electrochemical measurements suggest a good correlation among alloy composition, film thickness, relative permittivity as well as film resistance. It is inferred that the formation factor, k greater than unity and stable growth of compact composite film is attainable through thermodynamic selection of electrolyte and Gibbs free energy minimization criteria. Graphical abstract: Image, graphical abstract